A body without a head. (23rd August 2021) - Chavoshian, Ali; Park, Sophia
Abstract : Along with the recent development of various theories of the body, Lacan's body theory aligns with postmodern thinkers such as Michel Foucault and Maurice Merleau-Ponty, who consider the body to be social and not biological. Lacan emphasizes the body for the Real, the passive condition of the body in terms of formation, identity, and understanding. This condition of the body is further evident in the condition of bodies of women and laborers under patriarchy and capitalism, respectively. Lacan's 'not all' position, which is envisioned in the logical square diagram, allows women a way to question the system of patriarchy and opens up alternative sexual identities. Lacan's approach to feminine sexuality, when applied to women's spirituality, emphasizes multiple narratives of body, gender roles, and sexualities. In the social discernment and analyses of liberation theology, the capitalist discourse can be applied as a tool to understand how people are manipulated by late capitalist society without being aware of it. Lacan's theory of a 'body without a head' reflects the current condition of the human body, existing in a state of lack, but including possibilities for transforming society.